(untitled) (Carte Romanze, 2019)
The article analyses a little-known witness of Provençal sirventes BdT 217.2. The copy preserved in ms. Milano, Biblioteca Ambrosiana D 465 inf., cc. 262-263 belonged to Gian Vincenzo Pinelli and its main interest lies in the presence in its margins of several glosses in Italian language: their source is the same of the text itself and they seem to be the signs of a project to develop a complete translation of the sirventes. The article provides an edition, a classification and a translation-related analysis of these marginalia, in order to make assumptions about the anonymous – and particularly skilled in the subject of Provençal language – glossator’s identity and about how the text may have entered Pinelli’s library.